The effect of MRI contrast agents on hepatic and splenic uptake in the rabbit during 99mTc‐MDP bone scintigraphy. (2nd June 2015) - Qiu, Lin; Tang, Yuhui; Chen, Yue; Huang, Zhanwen; Zhu, Yan; Zhang, Li; Cai, Liang; Wan, Qiang; Feng, Yue
Abstract : The objective of this study was to investigate the effects of Omniscan® and Magnevist® on 99m Tc‐MDP uptake in rabbits during 99m Tc‐MDP bone scintigraphy. In Experiment Group 1, 30 healthy adult rabbits were randomized into six subgroups ( n = 5); each subgroup experienced a different time interval between injections (30 min, 60 min, 120 min, 240 min, 360 min, 24 h). All six subgroups were injected first with Omniscan®, then with 99m Tc‐MDP. After 7 days, the same six subgroups were injected with normal saline followed by 99m Tc‐MDP at the same time intervals. In Experiment Group 2, 20 healthy adult rabbits were allocated randomly to four subgroups ( n = 5); each subgroup experienced a different time interval between injections (30 min, 60 min, 120 min, 240 min). All four subgroups were injected first with Magnevist®, then with 99m Tc‐MDP. After 7 days, the same four subgroups were injected with normal saline followed by 99m Tc‐MDP. In all experiments, whole‐body skeletal imaging was performed. Liver, spleen, and background were delineated to determine the target‐to‐background (T/B) ratio. Diffusely increased intake of the imaging agent was seen in the liver and spleen when the injection‐time interval between Omniscan® and 99m Tc‐MDP varied from 30 min to 240 min and when the time interval between Magnevist® and 99m Tc‐MDP was 30 min–60 min. The imaging findings are consistent with the results of L/B and S/B ratios in each experiment group. Both Omniscan® and Magnevist® have an effect on 99m Tc‐MDP uptake during bone scanning; the main effect is diffusely increased hepatic and splenic activity. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The authors report the hepatic and splenic activity on SPECT imaging of rabbits which were injected with Omniscan® and Magnevist® and then with 99m Tc‐MDP 30, 60, 120, 240, and 360 min and 24 h later. The effects of Omniscan® and Magnevist® on the radiochemical purity of 99m Tc‐MDP were also investigated by TLC analysis. SPECT and TCL were combined to demonstrate that the abnormal uptake is strongly correlated to the half‐time of the MRI contrast agents in the body of rabbits.